Lurking in the dark: Cryptic Strongyloides in a Bornean slow loris. Issue 2 (August 2018) - Frias, Liesbeth; Stark, Danica J.; Lynn, Milena Salgado; Nathan, Senthilvel KSS.; Goossens, Benoit; Okamoto, Munehiro; MacIntosh, Andrew J.J.
Abstract: Within host communities, related species are more likely to share common parasitic agents, and as a result, morphological similarities have led researchers to conclude that parasites infecting closely related hosts within a community represent a single species. However, genetic diversity within parasite genera and host range remain poorly investigated in most systems. Strongyloides is a genus of soil-transmitted nematode that has been reported from several primate species in Africa and Asia, and has been estimated to infect hundreds of millions of people worldwide, although no precise estimates are available. Here we describe a case of infection with a cryptic species of Strongyloides in a Bornean (Philippine) slow loris ( Nycticebus menagensis ) living within a diverse community of several primate species in the Lower Kinabatangan Wildlife Sanctuary, Malaysian Borneo. Fresh fecal samples were collected from five primate species and nematode larvae cultured from these samples were selected for phylogenetic analyses. Sequences obtained for most larvae were identified as S. fuelleborni, grouping into three different clusters and showing no aggregation within specific hosts or geographic location. In contrast, a set of parasite sequences obtained from a slow loris clustered closely with S. stercoralis into a different group, being genetically distinct to sequences reported from other primate hosts, humans included. Our results suggest that although S. fuelleborni infects all haplorrhines sampled in this primate community, a different species might be infecting the slow loris, the only strepsirrhine in Borneo and one of the least studied primates in the region. Although more data are needed to support this conclusion, we propose that Strongyloides species in primates might be more diverse than previously thought, with potential implications for ecological and evolutionary host-parasite associations, as well as epidemiological dynamics. Graphical abstract: Image 1 Highlights: Cryptic Strongyloides lineage in a Bornean slow loris. Previously uncharacterized taxon, phylogenetically close to S. stercoralis. S. fuelleborni identified in four out of five sympatric primates.